RADIATION SAFETY MANAGEMENT SYSTEM FOR EMPLOYEES IN RADIOLOGY INSTALLATIONS dr. TADJUDDIN CHALID HOSPITAL - Widiastuty, Lilis; Rezky Wijaya, Dian; Ekasari, Ranti; Arranuri, Zilfadhillah; Habibi, Habibi; Azwar, Muhammad; Hasriani, Hasriani (Homes Journal: Hospital Management Studies Journal, 2022)
Background: Radiographers have duties and responsibilities related to radiation, so one must receive protection for occupational health and safety before starting work, while working or after finishing work, considering that a radiation worker’s job is related to X-rays that have characteristics can cause deterministic effects (tissue damage) and genetics. Objective: This study aims to find out in-depth information about the radiation safety management system for employees at the radiology installation at dr. Tadjuddin Chalid Hospital. Method: This study uses a qualitative method. The informants of this study were the head of the room and 2 radiation protection officers, a total of 3 people. Data was collected through in-depth interviews, observation, and documentation. Results: The results showed that radiation protection staff at the radiology installation of dr. Tadjuddin Chalid Hospital has attended radiation protection training organized by BAPETEN (Nuclear Energy Supervisory Agency), has a certificate and SIB (Work Permit), Initial and periodic health checks have been carried out, Radiation protection equipment owned in radiology installations is still inadequate and 5 the apron has a leak. Conclusion: It is hoped that the hospital management needs to ensure the implementation of a radiation safety management system at the radiology installation of dr. Tadjuddin Chalid Hospital, so that radiology employees have a sense of security and can work professionally.